FORMULASI TABLET EKSTRAK SAMBILOTO (Andrographis paniculata Nees) - , AWAL PRICHATIN KUSUMA DEWI, Prof. Dr. Sri Sulihtyowati Soebagyo, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
An investigation of the tablet formulation of Sambiloto (Andrographis paniculata Nees) extract, with Avicel PH 102 as filler-binder and Explotab as disintegrant, has been conducted. The aim of this study was to observe the influence of Avicel PH 102, Explotab and their interaction to the disintegration time of the tablet and dissolution of andrographolide (Q45), and to find out the optimum formula. For these purposes, factorial design was used with Avicel PH 102: 20% and 90%, Explotab: 2% and 8% of extract weight respectively. Tablet were produced by direct compression. The respon of disintegration time and dissolution andrographolide (Q45) were observed. Based on Yateâs treatment and anova analysis, Avicel PH 102 and Explotab significantly influenced to decrease the disintegration time, but their interaction tended to increase the disintegration time. At the other side, Avicel PH 102, Explotab and their interaction significantly increased the andrographolide dissolution (Q45) of the sambilotoâs extract tablet. Avicel PH 102 dominantly increased the dissolution (Q45) of andrografolid. Based on equations, contour plots and super imposed of the contour plots using Design Expert7.0.0, the optimum formula of sambilotoâs extract tablet was obtained with 78,1 â 87,55% Avicel PH 102 and 7,19 â 7,82% Explotab of the extract weight producing tablet with disintegration time of 4,02 â 10,03 minutes and andrographolide dissolution (Q45) of 75,30 â 82,44%.